Desentralisasi Dan Otonomi Daerah Dalam Upaya Penyelenggaraan Pemerintahan Daerah Yang Baik - Fernanda, M; Frinaldi, Aldri; Magriasti, Lince (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Regional autonomy as a form of decentralization of government policies is aimed at bringing the government closer to providing services to the community as a whole. Thus, the services provided tend to be more evenly distributed and in accordance with the needs of the community in the area concerned. Decentralization and regional autonomy can be said to be successful if government services to the community become better and the community becomes more involved in improving shared welfare. Delegation of authority from the central government to regional governments is carried out by taking into account the capacity and ability of local governments to organize and manage the interests of the local community. The implementation of good government is the main prerequisite for realizing the aspirations of the people in achieving the goals and ideals of the nation and state. The parameters of good regional government are in the form of service to the community and empowerment of community members in every development. In order for good local government to become a reality and run as it should, it requires commitment and active involvement of the local government and the community. Therefore, in the administration of regional government leadership is needed for regional heads who have the ability, are creative, responsive, honest, trustworthy, democratic, and obedient to principles and have leadership insights that are characterized by local wisdom. Thus, the wheel of regional government which is run on the principle of broadest autonomy is able to create good and accountable regional government.